Residential satisifaction in the new urban housing projects in Algeria: a case study of Ain-Allah, Algiers - Oussadou, Aomar (1988)
During the last few decades most developing countries have experienced a rapid growth in population which has resulted in rapid urbanisation in the form of new towns and an expansion of existing towns, coupled with an increasing dependance upon developed countries for the implementation of the new housing programmes. In Algeria, since Independance the problems of the high population growth and the rural-urban migration have led to a rapid growth of cities and towns. Since 1975 the Algerian government has been executing numerous housing programmes named ZHUN's (Zones d' Habitat Urbaines Nouvelles), the main objective being to build as many dwellings as possible in the shortest possible period of time to reduce the housing deficit. This policy has led to the construction of many new housing projects, consisting of stereotype "international style" buildings, very often built by foreign contractors with little appreciation of the life styles and requirements of the local people. This study is, in general, concerned with the effects of the problems of the new social and physical environments on the residents' level of satisfaction with the housing projects. The main objective of this study is to suggest a set of guidelines, or a development programme, for designing new urban housing projects which fulfill the requirements of the different socio-economic groups of residents and which will increase their level of satisfaction. The case study (Ain-Allah) is one of nine new housing projects (ZHUN's) in Algiers, some of which are still being constructed. The case study has similar physical features to those of the majority of the ZHUN's. With regard to its social structure, however, it is occupied by residents with different social characteristics and backgrounds. The ZHUN's are generally occupied by people from the colonial areas, but residents in Ain-Allah are composed of two distinct groups; those who moved from the traditional area of Algiers (the Casbah) and those who moved from the Western style areas (Colonial areas). These two groups did not only move from two different physical settings, but they also have different socio-economic characteristics. The case study is representative of most social and physical features of the ZHUN's, as discussed in greater detail in the next chapter. In addition, it provides the opportunity to examine how different social groups react to the same physical environment. Findings reveal that satisfaction with the new project is influenced by residents' previous experience. Residents originating from a traditional setting (Casbah) tend to evaluate their new environment mainly by the cohesion and level of friendship between neighbours, whilst those from the western style (colonial) areas tend to attribute more importance to quality of the physical environment. When planning a new project, emphasis should not only be placed on the spatial organisation of the built form, but also on the selection of the residents and their level of homogeneity. Many researchers have argued that outdoor common spaces provide the opportunity for social contacts between residents, which in turn, encourage the process of friendship formation between them. In this research, however, findings show that the arrangement of the new buildings around large common outdoor spaces with direct visual contact affected the level of privacy of the flats. This has, consequently, hindered residents' familiar outdoor social activities and slowed down the rate of friendship formation between them. On account of the Islamic culture, based on segregation between males and females, spaces used by men (outdoor open spaces) should not be in direct visual contact with the flats which are mainly used by women, in particular housewives. The process of friendship formation is also found to be much more rapid between neighbours who originated from the same area than between those who moved as strangers and did not work together. The latter required longer for integration to the new community. Also, people working together make friends more quickly than those who do not. It is also found that the new built form affects the rate of friendship formation. Proximity of the new flats and sharing the same landing, staircases and building access encourage social contacts between residents. A comparison between a housing cluster (cluster three) occupied by heterogeneous groups (Casbah and colonial areas) and two clusters (clusters one and two) occupied only by homogeneous groups (cluster one occupied by people from the Casbah and cluster two by people from colonial areas) revealed that friendliness, but not necessarily friendship, existed between heterogeneous residents living in the same cluster (cluster three). It was also found that physical proximity between homogeneous residents (in both clusters one and two) promoted friendship formation between them. However, findings show that no social relationships existed between the two heterogeneous groups living separately (clusters one and two). To promote friendliness between heterogeneous residents and friendship between homogenous residents, this research suggests that when allocating the flats, buildings should be occupied by homogenous residents, and basic housing units by heterogenous residents. Findings also reveal that satisfaction with the outdoor spatial organisation is related to the function of the outdoor spaces. For example, when comparing levels of satisfaction with outdoor common spaces in a basic housing unit composed of residential buildings and a basic housing unit with facilities at the ground floor of its buildings, it was found that a higher number of people in the former were satisfied. The common space in the basic housing unit with facilities was transformed from a quiet semi-public space for local residents to a public space where people from all parts of the project come to do their shopping. This resulted in both a loss of privacy and noise disturbance. According to the literature, the size of a housing area, or the catchment area, is determined by the location of the primary school and shops. It suggests that these facilities should not be located at more than 5 to 7 minutes' walking distance (around 500m) from the furthest dwelling. In this research, however, it is found that the majority of people living at less than 10 minutes' walking distance (650m to 700m) from these facilities were satisfied with their location. The new projects can, therefore, have a larger catchment area than those proposed by the literature and the CNERU. Findings also suggest that it is more economical and satisfactory to locate the new housing projects as close as possible to existing commercial centres. This would not only reduce the cost of connecting a new project to water, gas, electricity and sewage systems, but would also ease the use of the facilities of the nearby commercial centre(s) by the new residents. Finally, specific measures are recommended for planning and designing new urban housing projects. It is necessary to provide an environment which allows easy integration to the new community, and with which residents can identify and be satisfied. This is possible to achieve by understanding the socio-economic and cultural characteristics of the residents, by housing these residents in such a way as to encourage friendship formation between them, and by providing a new built form which fulfills the requirements of the residents and which does not hinder their familiar social activities.